SCALE DEVELOPMENT STAGES SPECIFIC TO HEALTH LITERACY (Turkey Health Literacy Journal, 2023)
This review was written by following the scale development stages specific to health literacy, in order to help academicians who will develop a scale approach systematically, and also to facilitate their studies by providing easier access to information on the subject.